Identifying regularities of fluid throttling of an inertial hydrodynamic installation - Nussupbekov, Bekbolat; Oshanov, Yerlan; Ovcharov, Michael; Kutum, Bayan; Duisenbayeva, Мoldir; Kongyrbayeva, Aitkul (Eastern-European Journal of Enterprise Technologies, 2023)
The article presents the results of experimental research conducted on a specially designed setup for pressurizing various types of fluids through throttle orifices. To determine the optimal operating mode of the thermal system, throttle nozzles of different diameters, specifically 1.5 mm, 2 mm, and 3 mm, were utilized. One of the primary advantages of vortex heaters is their high heat exchange efficiency. This is attributed to the vortical motions and turbulence generated within the device, which promote more vigorous fluid mixing, thus enhancing heat transfer efficiency. However, vortex heaters do have certain drawbacks. Vortical components may experience wear and require regular maintenance and replacement. Subsequently, during the course of experimental work, an alternative inertia-based hydrodynamic system for heating heat carriers was developed and installed in a laboratory experimental facility. The research focus was on technical water. The results indicated that the static pre-pressure generated by the supply of water from the water main into the system decreases as the rotor's angular velocity increases. Experimental investigations demonstrated that rotor rotation leads to a redistribution of flow characteristics in throttle orifices for both static and dynamic inertial fluid discharge. Given that any static column of liquid results in level flow through throttle orifices, their flow static parameters were established. Furthermore, the research revealed that with the increase in rotor angular velocity, the fluid pressure at the throttle orifices rises, while the share of fluid discharge from the initial static pressure decreases in the overall fluid flow